2015
DOI: 10.15252/embj.201490350
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the human U sn RNP assembly machinery reveals stepwise Sm protein organization

Abstract: The assembly of spliceosomal U snRNPs depends on the coordinated action of PRMT5 and SMN complexes in vivo. These trans-acting factors enable the faithful delivery of seven Sm proteins onto snRNA and the formation of the common core of snRNPs. To gain mechanistic insight into their mode of action, we reconstituted the assembly machinery from recombinant sources. We uncover a stepwise and ordered formation of distinct Sm protein complexes on the PRMT5 complex, which is facilitated by the assembly chaperone pICl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 63 publications
(137 reference statements)
6
60
0
1
Order By: Relevance
“…However, it is not impossible that an as yet unidentified RNA-binding protein unrelated to Gemin5 may transiently associate with the SMN complex to fulfill the role of Gemin5. Another concern is that Gemin5 appears to be not needed for snRNP assembly in vitro (Neuenkirchen et al 2015). There are several possible explanations for this observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not impossible that an as yet unidentified RNA-binding protein unrelated to Gemin5 may transiently associate with the SMN complex to fulfill the role of Gemin5. Another concern is that Gemin5 appears to be not needed for snRNP assembly in vitro (Neuenkirchen et al 2015). There are several possible explanations for this observation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed a special U1 snRNP assembly pathway dependent on the U1-70K protein, which binds SL1 (So et al 2016). This finding perhaps explains the observation that Gemin5 is not strictly needed for snRNP assembly in vitro, judged by an assay using purified systems (Neuenkirchen et al 2015). The binding of the SMN complex and Gemin5 to the Sm site is sequence-specific, but the nucleotide sequence for the stem-loop appears to be unimportant.…”
mentioning
confidence: 89%
“…Whereas other members of the pathway monomethylate or asymmetrically dimethylate arginine residues, PRMT5 symmetrically dimethylates arginine residues (reviewed by Bedford and Clarke, 2009;Stopa et al, 2015). Regulating a diverse set of target proteins, it can methylate specific Sm proteins, facilitating their assembly into a core complex of spliceosomal snRNPs (Chari et al, 2008;Meister and Fischer, 2002;Neuenkirchen et al, 2015;Pelz et al, 2015). Additionally, PRMT5 can regulate gene expression by methylation of histones H2A/H4 and H3 (specifically H2A/H4R3 and H3R8), which are generally associated with transcriptional repression (Ancelin et al, 2006;Di Lorenzo and Bedford, 2011;Lee and Bedford, 2002;Tee et al, 2010;Zhang et al, 2015;Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The assembly of the human Sm ring around the Sm RNA site is an intricate and ordered process mediated by the SMN complex, comprising the SMN (survival motor neuron) protein and several Gemin proteins, and other factors (Liu et al 1997;Zhang et al 2011;Grimm et al 2013;Neuenkirchen et al 2015). Mutations in the human SMN1 gene are the cause of the disease spinal muscular atrophy (Lunn and Wang 2008;Chari et al 2009).…”
Section: Introductionmentioning
confidence: 99%